Effect of intensification on grow out of the Amazon River prawn, Macrobrachium amazonicum - Moraes-Valenti, Patricia M. C.; Valenti, Wagner Cotroni [UNESP] (Blackwell Publishing, 2007)
The effects of intensification on growth, survival, productivity, population structure, and distribution of harvested biomass in individual size classes of Macrobrachium amazonicum in semi-intensive culture were evaluated. Postlarvae (0.01 g) were stocked in 12 ponds at densities of 10, 20, 40, and 80/m(2) (three replicates per treatment) and raised for 5.5 mo. Average individual weight significantly decreased and productivity significantly increased as stocking density increased (P < 0.001), while survival was not affected (P > 0.05). Prawn mean weight at harvest ranged from 3.6 (80/m(2)) to 7.0 g (10/m(2)). Average survival ranged from 65.5% (40/m(2)) to 72.8% (20/m(2)), while productivity ranged from 508 (10/m(2)) to 2051 kg/ha (80/m(2)). Harvested biomass showed a clear bimodal distribution in individual size classes indicating the occurrence of heterogeneous growth, which may affect management and market strategies. Harvested biomass of prawns weighing more than 7 g (the best market size) increases for stocking densities up to 40/m(2) and stabilizes between 40 and 80/m(2). Growth reduction was associated with a decreasing frequency and average weight of green claw 1 and green claw 2 male morphotypes and adult females as density increased. Thus, the distribution of male morphotypes and sexually mature females are affected by density-dependent factors. Results suggest that prawn density plays an important role on M. amazonicum grow-out phase, as has been demonstrated for other species of the genus Macrobrachium. M. amazonicum tolerates grow-out intensification and may be raised in both semi-intensive and intensive systems stocked at very high densities yielding high productivity.